Answer:
x = 3.89
x = 4............... approximately'
y =6.889
y = 7................ approximately
Explanation:
let
-3x+3y=9 ...................equation 1
2x-7y=-14.................... equation 2
from equation 1
-3x+3y=9 ...................equation 1
3y = 9 + 3x
divide both sides by 3
3y/3 = ( 9 + 3x)/3
y = ( 9 + 3x)/3......................equation 3
put the value of y = ( 9 + 3x)/3 in equation 2
2x-7y=-14.................... equation 2
2x - 7(9+3x)/3 = -14
2x - (63 + 21x)/3 = -14
multiply through by 3
3(2x) - 3 (63 + 21x)/3 = 3(14)
6x - 63 + 21x = 42
collect the like terms -11.667
6x+21x = 42+ 63
27x = 105
divide both sides by 27
x = 105/27
x = 3.89
x = 4............... approximately'
substitute for the value of x in equation 3
y = ( 9 + 3x)/3......................equation 3
y = ( 9 + 3(3.89) )/3
y = (9 + 11.67)/3
y = 20.667/3
y =6.889
y = 7................ approximately
to check for the correctness of your answer put the value of x and y in either equation 1 or equation 2, then u will observe the LHS= RHS
-3x+3y=9 ...................equation 1
-3(3.889) + 3(6.889) = 9
9 = 9 ......................... PROVED